Teologi Bencana Menurut Qurais Shihab dan Implikasinya Bagi Bencana di Indonesia - Moh. Syafi’ (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2017)
This article attempts to look at the phenomenon of natural and social disasters and the recent solutions that often occur in Indonesia through the interpretation of Qurais Shihab by the semanatic method it uses. Through the semantic approach, the term disaster according to Qurais Shihab is as follows: bala ‘,’ fitnah, mushibah and ‘adzab. Each term used by al-quran to refer to the disaster has different characters, terminology and objects that cause the Qur’an and human point of view to disasters are also different. The solution offered is to look at the character of the existing disaster. If the disaster is caused by an indirect cause, then this kind of disaster cannot be avoided, because the occurrence is indeed the provision of “destiny” of God (natural disaster). What can be done is preventive measures and emergency response steps after a disaster. Secondly, man-made disasters are not doing things that lead to the destruction of nature and mankind.